Sn-protoporphyrin suppresses chemically induced experimental hepatic porphyria. Potential clinical implications. - Galbraith, R A (1985)
The ability of Sn(tin)-protoporphyrin to inhibit the induction of hepatic delta-aminolevulinate (ALA) synthase by allylisopropyl acetamide (AIA) was examined in the adult rat. Doses of Sn-protoporphyrin of 1, 10, and 50 mumol/kg body wt resulted in decreases in AIA-induced hepatic ALA-synthase activity of 32, 52, and 60%, respectively, compared with rats treated with AIA alone; inhibition of ALA-synthase was not a direct effect of Sn-protoporphyrin. This inhibition of the enzyme activity in liver was reflected in concurrent decreases in urinary excretion of ALA and porphobilinogen (PBG). The increased urinary excretion of ALA and PBG observed following AIA treatment was reduced by the lowest dose of Sn-protoporphyrin (1 mumol/kg body wt) and abolished completely by the higher doses of the metalloporphyrin (10 and 50 mumol/kg body wt). These findings in a rat model of hepatic porphyria suggest that Sn-protoporphyrin may be useful in the treatment of acute exacerbations of "inducible" hepatic porphyrias in man, especially since Sn-protoporphyrin, unlike hematin which is presently used for this purpose, is neither degraded by nor induces the activity of heme oxygenase.